2015
DOI: 10.18043/ncm.76.5.315
|View full text |Cite
|
Sign up to set email alerts
|

Research and Operations: Joining Forces to Improve Care for Veterans

Abstract: The Veterans Health Administration's move to adopt a joint operations-research perspective in promoting clinical innovation in the health care system has led to an increasing number of researchers, clinicians, and policy leaders collaborating on quality improvement activities. We describe 2 such programs, both aimed at improving care for older veterans, which were conducted by teams with both research and operations experience. We explore differences in perspectives, contributions, and roles of various team me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…18 Enhancing Quality of Prescribing Practices for Veterans Discharged from the Emergency Department (EQUiPPED) is one project that has aimed to decrease PIM prescribing in an older veteran population seen in the ED. [19][20][21][22][23] The EQUiPPED intervention consisted of 3 main components: provider education through academic detailing, clinical decision support, and provider feedback on prescribing practices. 19 EQUiPPED has been able to show a decrease in PIM rates by ED prescribers through education, clinical decision support, and prescribing feedback.…”
Section: Introductionmentioning
confidence: 99%
“…18 Enhancing Quality of Prescribing Practices for Veterans Discharged from the Emergency Department (EQUiPPED) is one project that has aimed to decrease PIM prescribing in an older veteran population seen in the ED. [19][20][21][22][23] The EQUiPPED intervention consisted of 3 main components: provider education through academic detailing, clinical decision support, and provider feedback on prescribing practices. 19 EQUiPPED has been able to show a decrease in PIM rates by ED prescribers through education, clinical decision support, and prescribing feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Initial program evaluation found that STRIDE participants were more likely to be discharged to home than skilled nursing or rehabilitation compared to clinically similar patients receiving usual care (92% vs. 74%, p = 0.007) [22]. Based on the cumulative evidence on early mobility and the positive results from the STRIDE demonstration, the Durham VAHCS established STRIDE as a permanent clinical service in 2013 [23].…”
Section: Assisted Early Mobility For Hospitalized Older Veterans: Thementioning
confidence: 99%
“…Based on the cumulative evidence on early mobility and the positive results from the STRIDE demonstration, Durham VAHCS established STRIDE as a permanent clinical service in 2013 [23].…”
Section: Assisted Early Mobility For Hospitalized Older Veterans: Thementioning
confidence: 99%